2007
DOI: 10.1007/s11120-007-9134-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis: the peroxydicarbonic acid cycle in photosynthetic oxygen evolution

Abstract: Peroxydicarbonic acid (Podca), a proposed intermediate in photosynthetic oxygen evolution, was synthesized electrochemically. Consistent with literature descriptions of this compound, it was shown to be a highly reactive molecule, spontaneously hydrolyzed to H2O2, as well as susceptible to oxidative and reductive decomposition. In the presence of Mn2+ or Co2+, Podca was quickly broken down with release of O2. The liberation of O2, however, was partially suppressed at high O2 concentrations. In the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For mechanistic considerations, the following characteristics must be taken into account: (i) water is the direct substrate for dioxygen formation (Clausen et al 2005;Hillier et al 2006) without any catalytic function of bicarbonate (for a proposal, see Castelfranco et al 2007) that is not a constituent of the WOC (Ulas et al 2008;Shevela et al 2008); (ii) the S i -state transitions are coupled with proton release in a MS-EPT manner (for a discussion, see Meyer et al 2007); (iii) the oxidation steps of the WOC by Y OX Z are not limited by the rate of nonadiabatic ET but triggered by proton transfer (PT) and/or conformational changes and become blocked below threshold temperatures (for compilation of data, see Renger G 2001) and hydration levels (Noguchi and Sugiura 2002) that depend on the redox state S i ,; and (iv) the redox steps Y OX Z S 0 ! Y z S 1 and Y OX Z S 1 !…”
Section: Mechanismmentioning
confidence: 99%
“…For mechanistic considerations, the following characteristics must be taken into account: (i) water is the direct substrate for dioxygen formation (Clausen et al 2005;Hillier et al 2006) without any catalytic function of bicarbonate (for a proposal, see Castelfranco et al 2007) that is not a constituent of the WOC (Ulas et al 2008;Shevela et al 2008); (ii) the S i -state transitions are coupled with proton release in a MS-EPT manner (for a discussion, see Meyer et al 2007); (iii) the oxidation steps of the WOC by Y OX Z are not limited by the rate of nonadiabatic ET but triggered by proton transfer (PT) and/or conformational changes and become blocked below threshold temperatures (for compilation of data, see Renger G 2001) and hydration levels (Noguchi and Sugiura 2002) that depend on the redox state S i ,; and (iv) the redox steps Y OX Z S 0 ! Y z S 1 and Y OX Z S 1 !…”
Section: Mechanismmentioning
confidence: 99%
“…Since 1995, various data have been accumulated showing that bicarbonate is indeed functional in oxygen evolution ,,, . In addition to the earlier proposal of a catalytic intermediate ,, , it has been suggested that bicarbonate functions as a ligand to the Mn cluster or an integral cofactor of OEC ,,, , a cofactor crucial in the photoassembly process of the Mn cluster as a transient ligand to Mn ions ,,, , , a proton transfer mediator bound to a residue in the vicinity of the Mn cluster , and an element to indirectly stabilize OEC by binding to PSII proteins or extrinsic proteins ,, .…”
mentioning
confidence: 99%
“…Since 1995, various data have been accumulated showing that bicarbonate is indeed functional in oxygen evolution ,,, . In addition to the earlier proposal of a catalytic intermediate ,, , it has been suggested that bicarbonate functions as a ligand to the Mn cluster or an integral cofactor of OEC ,,, , a cofactor crucial in the photoassembly process of the Mn cluster as a transient ligand to Mn ions ,,, , , a proton transfer mediator bound to a residue in the vicinity of the Mn cluster , and an element to indirectly stabilize OEC by binding to PSII proteins or extrinsic proteins ,, . In fact, the X-ray structure by Ferreira et al at 3.5 Å resolution tentatively assigned a part of the nonprotein density to bicarbonate as a ligand bridging Mn and Ca ions.…”
mentioning
confidence: 99%
“…Currently, the way bicarbonate is possibly involved in the events on the donor side of PSII has had many speculations. The two viewpoints considering bicarbonate as an intermediate substrate for photosynthetic water oxidation or as a direct ligand of Mn4CaO5 cluster are thought to be unlikely since no strong experimental evidence exists or supports it [10,11]. There are suggestions that bicarbonate may play a role in stabilizing the OEC indirectly by binding to extrinsic proteins or some other nearby protein components [12,13], which, however, needs to be investigated.…”
Section: Introductionmentioning
confidence: 99%